Dekonstruksi Epistemologi Muhammad Shahrur - Suheri Sahputra Rangkuti (AL-ISTINBATH : Jurnal Hukum Islam, 2018)
The past viewpoint of issuing fiqh policy was strongly influenced by episteme (in Arkoun) in his time. Of course this is not the point of the problem at this time.The main problem is to draw the building of past thinking, both in the epistemological realm and in the axiology level. Finally, many fiqh are merely swell and attempts to rationalize the classical mass construct without dismantling and rebuilding from scratch. This fiqh policy must inevitably clash with the present, for example, fiqh about women, which closes a lot of their space, because classical masculine and patriarchal epistemes make them lose their independence even considered inappropriate even if they only determine the direction of their lives. Shahrur came by reading and deconstructing the epistemology in women's fiqh so as to produce friendly fiqh in the present nuance. Although the way he traveled was classified as not mainstream, the mega project he handled was worthy of investigation and discussion.